2019
DOI: 10.1186/s13054-019-2673-5
|View full text |Cite
|
Sign up to set email alerts
|

Cumulative fluid accumulation is associated with the development of acute kidney injury and non-recovery of renal function: a retrospective analysis

Abstract: BackgroundAcute kidney injury (AKI) is common in patients in the intensive care unit (ICU) and may be present on admission or develop during ICU stay. Our objectives were (a) to identify factors independently associated with the development of new AKI during early stay in the ICU and (b) to determine the risk factors for non-recovery of AKI.MethodsWe retrospectively analysed prospectively collected data of patients admitted to a multi-disciplinary ICU in a single tertiary care centre in the UK between January … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
1
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 26 publications
1
32
1
4
Order By: Relevance
“…A similar trend was found in a study from the United Kingdom that demonstrated a link between 48-hour FB and AKI non-recovery. 21 However, that study did not explore the data further and failed to point out to what extent positive or negative 48-hour FB would promote renal dysfunction. The present study might promote the conclusion by specifically and accurately demonstrating the relationship between 48hour FB and AKI progression because the 48-hour FB <À5% or >3% was associated with the risk of AKI progression (FB <À5% [OR 7.078; p = 0.031]; FB 3%-5% [OR = 6.598; p = 0.020]; FB >5% [OR 16.453; p < 0.001]).…”
Section: Discussionmentioning
confidence: 97%
“…A similar trend was found in a study from the United Kingdom that demonstrated a link between 48-hour FB and AKI non-recovery. 21 However, that study did not explore the data further and failed to point out to what extent positive or negative 48-hour FB would promote renal dysfunction. The present study might promote the conclusion by specifically and accurately demonstrating the relationship between 48hour FB and AKI progression because the 48-hour FB <À5% or >3% was associated with the risk of AKI progression (FB <À5% [OR 7.078; p = 0.031]; FB 3%-5% [OR = 6.598; p = 0.020]; FB >5% [OR 16.453; p < 0.001]).…”
Section: Discussionmentioning
confidence: 97%
“…In a large French cohort, 5242 patients were included from 23 ICUs, 2458 patients were in stage 1 Critical Care Research and Practice (46.89%) [35], and in another Chinese cohort with a total of 3107 patients with AKI, 23.1% of these patients was in stage 1 [4]. A cohort from UK by Zhang et al which included 2525 patients with AKI in ICU showed around 41.2% of patients was in stage 1 [36].…”
Section: Discussionmentioning
confidence: 99%
“…12 Critical Care and Preoperative Medicine Research Group, Centre for Translational Medicine and Therapeutics, William Harvey Research Institute, Queen Mary University of London, London, UK. 13 Science Service Center, Kuopio University Hospital, Kuopio, Finland. 14 Centre for Integrated Critical Care, School of Medicine, The University of Melbourne, Melbourne, Australia.…”
Section: Supplementary Informationmentioning
confidence: 99%
“…While fluid therapy is the traditional cornerstone of AKI prevention and treatment [6], patients with AKI are also especially prone to develop fluid overload [7]. Such fluid overload is associated with increased mortality [7][8][9][10][11] and progression of AKI [12,13]. Thus, a more restrictive fluid management approach among adequately resuscitated patients with AKI might improve outcomes by reducing congestion and improving kidney and other organ function.…”
Section: Introductionmentioning
confidence: 99%